THE IMPACT OF THE COVID 19 PANDEMIC ON THE INDONESIAN TRADE SECTOR - Adiman, Sumardi; Junawan, Junawan (International Proceeding of Law and Economic, 2020)
The purpose of this study is to see the impact of the Covid-19 pandemic on the Indonesian trade sector. This study uses a qualitative descriptive method with observation and documentation methods. The results showed that the rate of economic growth in Indonesia could be influenced by China's economic growth. If the Chinese economy experiences a 1-2% slowdown, it will have an impact on the Indonesian economy by 0.1-0.3% to the Indonesian economy. Therefore, the Government of Indonesia needs to diversify the export markets of the main destination countries, such as countries in Africa or South America. It is time for Indonesia to reduce its dependence on imported goods from China.